Corrosion inhibition efficiency of water soluble ethoxylated trimethylol propane by gravimetric analysis - A.A. Abdel-Azim; R. Milad; R. El-Ghazawy; R. Kamal (Egyptian Journal of Petroleum)
Polyoxyethylenated trimethylol propane monolaurate surfactants with varied ethylene oxide content were tested as corrosion inhibitors via the weight loss method. Weight loss measurements for carbon steel dissolution were performed in 1 N HCl containing different inhibitor concentrations at 30, 40 and 50 °C. These measurements were utilized for calculating corrosion rate, surface coverage area and percentage inhibition. The obtained data show that the adsorption of these inhibitors obeys Langmuir adsorption isotherm. Thermodynamic parameters (ΔG∗, ΔH∗ and ΔS∗) of the corrosion process are evaluated and correlated to inhibitors structures.